Crisis leadership: The new imperative for MBA curricula. Issue 3 (November 2021) - Hertelendy, Attila J.; McNulty, Eric; Mitchell, Cheryl; Gutberg, Jennifer; Lassar, Walfried; Durneva, Polina; Rapp, Devin
Abstract: Given the increasing frequency of and high risk inherent in crises, Masters of Business Administration (MBA) should include crisis leadership as part of their core program offerings. This study aims to explore if leadership courses are taught as either a core or elective course in Advance Collegiate Schools of Business (AACSB) accredited MBA programs, and if any of these programs teach crisis leadership courses specifically. Based on a web-based search of AACSB schools offering MBA programs, crisis leadership is minimally represented across MBA programs, with 3.2% of business schools examined including a crisis leadership course as part of their curricula. Leadership courses are more commonly included as part of MBA programs' curricula, with 64.8% of business schools offering these courses. These leadership courses could set a foundation for MBA programs to begin embedding crisis leadership content specifically into their core curricula. Highlights: Only 64.8% of AACSB accredited business schools are currently teaching leadership courses. Few AACSB accredited business schools are currently teaching a crisis leadership course as part of their MBA curriculum. The ability to manage chronic crisis in a turbulent world requires additional competencies to be taught in crisis leadership. Leaders will need to be provided an opportunity to practice both table top or virtual scenarios.